The different response of PM2.5 stimulated nasal epithelial spheroids in control, asthma and COPD groups - Paulina Misiukiewicz-Stępień; Elwira Zajusz-Zubek; Katarzyna Górska; Rafał Krenke; Magdalena Paplińska-Goryca (Respiratory Research)
Abstract Background Pathobiology of asthma and chronic obstructive pulmonary disease (COPD) is associated with changes among respiratory epithelium structure and function. Increased levels of PM2.5 from urban particulate matter (UPM) are correlated with enlarged rate of asthma and COPD morbidity as well as acute disease exacerbation. It has been suggested that pre-existing pulmonary obstructive diseases predispose epithelium for different biological response than in healthy airways. The aim of this study was to assess the impact of PM2.5 on the biological response of healthy as well as asthma and COPD respiratory epithelium using 3D/spheroid culture model. Methods The spheroids from 5 healthy controls, 8 asthma patients, and 8 COPD patients were exposed to 100 µg/ml of PM2.5 for 24 h. Results The common pattern for healthy asthma and COPD epithelium inflammatory response to PM2.5 stimulation include the increase in IL-1β, IL-6, IL-8 mRNA expression, and secretion of IL-6. Asthmatic spheroids produced higher amount of TNF-α and IL-8, whereas COPD spheroids expressed increased mRNA level of MUC5AC and decreased level of MMP7. PM2.5 treatment induced changes in AHR and TLR4 expression on secretory epithelium in COPD. Conclusion The response of airway epithelium to air pollution is different in healthy people than in obstructive lung disease patients. The impairment of airway epithelium in asthma and COPD changes their response to toxic environmental stimuli. This physiological dysfunction might be associated with diseases exacerbation of obstructive lung diseases.